Exploring the Relationship Between Faculty Training and School Performance in Kathmandu Valley: A Comparative Study of Community and Institutional Schools - Ojha, Sateesh Kumar; Shrestha, Shyam Sundar (A Bi-annual South Asian Journal of Research & Innovation, 2023)
This article tries to uncover the present training and development pattern of faculties of community and institutional schools in Kathmandu Valley and their relation with performance. The method adopted is the descriptive and inferential analysis survey questionnaire. Rating scales were used, and the sample size was 160 schools: 80 institutional schools and 80 community schools. The findings from the research signify the resultant performance of institutional training differed significantly, but the training patterns were not different in aggregate. However, critical analysis of training showed the differences in the focus of training: institutional schools focus on the essential skills of the faculty and training new faculty when they enter. The findings implicate the fourth coming training of schools’ faculties.